TRANSFORMATIONAL LEADERSHIP IN THE SERVICE OF ORGANIZATIONAL CHANGES - Matejić, Ivica; Ćurčić, Mihailo; Kostić, Radan (Journal of process management and new technologies, 2021)
The complex and dynamic environment in which modern companies operate requires frequent organizational changes that are used as a mechanism for adapting the company's business to market requirements, in order to improve or maintain a competitive advantage. Mergers and acquisitions, as a complex form of organizational change of companies, represent a relevant problem area of ​​research. Since the success of organizational change depends on two important factors, leaders and employees, the aim of this research is to identify the interdependence of transformational leadership, job satisfaction and commitment to organizational change by employees in the post-acquisition period. The research results show that there is interdependence between transformational leadership, job satisfaction and commitment to organizational change in the post-acquisition period. The empirical research was conducted in 2021, using a survey method. Data were analyzed using Pearson’s correlation and single as well as multiple regression method. A sample of 129 respondents was taken into accounts, who are employed in companies in the Republic of Serbia that have gone through the acquisition process in the last five years.